Pengaruh Pemberian Poster Dalam Meningkatkan Persepsi tentang Succesful Aging Pada Lanjut Usia - Dian Novita Siswanti (Journal of Innovative and Creativity, 2025)
Successful aging is related to the problem of naturally changing an individual's role in society (retiring) or continuing to have the same activities as when he was young (Kaplan, 1998). It is very important to know these stages of change so that individuals can reach a happy and healthy old age. The project carried out aims to provide psychoeducation through the distribution of posters on social media, namely Instagram. The posters contain an explanation of what successful aging is and the factors that cause successful aging. It is hoped that the posters distributed will be able to provide guidance and strategies for achieving a successful old age by remaining active, thinking positively, and maintaining good social relationships. The steps in project implementation are psychoeducational planning such as searching for references and compiling materials. Then implement psychoeducation such as distributing posters and posttests. And finally, preparing the results report. From distributing this poster, it received 86 likes and 21 comments. Apart from that, based on the post-test results that were distributed, 40 feedback was obtained from willing respondents. From the respondents' answers, it can be seen that the respondents gained knowledge about successful aging.